2020
DOI: 10.1108/aia-09-2019-0030
|View full text |Cite
|
Sign up to set email alerts
|

Increasing social engagement among college students with autism

Abstract: Purpose Many university-based services for individuals with autism spectrum disorder (ASD) have incorporated peer mentorship programs; however, the research on the success of these programs to increase social engagement is extremely limited. This study aims to examine the effectiveness of a peer mentor program, both alone and combined with an incentive program, on increasing the social engagement of college students with ASD. Additionally, the perceptions of college students with ASD were also examined to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…18 Autistic students have also identified a desire for group time that is purely social, 18 which several peer mentorship programs included as a component of their program. 63,64 Overall, the peer mentorship programs reviewed in this article allow for more flexibility in terms of focus and format than traditional postsecondary accommodations. Thus, it is clear that peer mentorship programs have the potential to meet several of the identified support needs of autistic postsecondary students.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…18 Autistic students have also identified a desire for group time that is purely social, 18 which several peer mentorship programs included as a component of their program. 63,64 Overall, the peer mentorship programs reviewed in this article allow for more flexibility in terms of focus and format than traditional postsecondary accommodations. Thus, it is clear that peer mentorship programs have the potential to meet several of the identified support needs of autistic postsecondary students.…”
Section: Discussionmentioning
confidence: 99%
“…65 Gillespie-Lynch et al 66 reported reduction in the severity of autistic symptoms in the spring semester (2013), but not the fall semester (2013), data collection. Thompson et al 63 reported significant improvements in social awareness, communication, and motivation (i.e., dimensions of social responsiveness) among participants.…”
Section: Effectiveness Of Identified Peer Mentoring Programsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have noted the poorer quality of life experienced by adult persons with autism; notably increased mental health problems, low employment and poor social integration (Ayres et al , 2018; Howlin and Magiati, 2017). Nonetheless evidence is growing that quality of life improvements is associated with increased informal social support and membership of support groups (Tobin et al , 2014); participation in social skills training (Gates et al , 2017), opportunities for self-determination (Kim, 2019), developing friendships and social networks particularly with other autistic people (Milton et al , 2018; Sosnowy et al , 2019; Crompton et al , 2020) and peer mentoring (Fairchild et al , 2020).…”
Section: Introductionmentioning
confidence: 99%